PENGARUH MEDIA PEMBELAJARAN SHORT MESSAGE GUIDED TERHADAP PRESTASI BELAJAR KIMIA MATERI POKOK IKATAN KIMIA DI MASA PANDEMI COVID-19: THE EFFECT OF SHORT MESSAGE GUIDED LEARNING MEDIA ON CHEMISTRY LEARNING ACHIEVEMENTS IN CHEMICAL BONDING TOPIC IN THE TIME OF COVID-19 PANDEMIC ERA - Syarifatul Mubarak (UIN Mataram, 2021)
This study aims to determine the effect of short message guided learning media on student achievement on chemical bonding material. This type of research is a posttest control design research. Where sampling is done by simple random sampling which is then given a formative test instrument at the end of the lesson and analyzed using student t-test analysis to find out whether there are differences in student achievement with the short message guided media. The results of the analysis found that the short message guided media was able to have a positive influence on the chemistry learning achievement of class X students on chemical bonding material, this was indicated by the t-test result of 2.0248 which was greater than t-table of 1.666 at a significance level of 5%. Because tcount > ttable, it can be concluded that there is a significant difference between student achievement in the experimental class and the control class. Another result found that as many as 99.7% of students stated that the learning content presented via SMS was quite helpful to very helpful in understanding the material presented in class. Other data shows that 90.70% agree and strongly agree that the content presented via SMS can remind the subject matter that has been learned in class. Penelitian ini bertujuan untuk mengetahui pengaruh media pembelajaran short message guided terhadap prestasi belajar siswa pada materi ikatan kimia. Jenis penelitian ini merupakan penelitian posttest control design. Di mana pengambilan sampel dilakukan dengan simple random sampling yang kemudian diberikan instrument tes formatif pada akhir pembelajaran dan dianalisis menggunakan analisis student t-test untuk mengetahui apakah terdapat perbedaan prestasi belajar siswa dengan adanya media short message guided. Hasil analisis menemukan bahwa media short message guided mampu memberikan pengaruh positif terhadap prestasi belajar kimia siswa kelas X pada materi ikatan kimia, hal ini ditandai dengan hasil uji thitung sebesar 2.0248 yang lebih besar dari ttabel 1.666 pada taraf signifikansi 5%. Karena thitung > ttabel, maka dapat disimpulkan bahwa terdapat perbedaan yang signifikan antara prestasi belajar siswa di kelas eksperimen dengan kelas kontrol. Hasil lain ditemukan bahwa sebanyak 99,7% siswa menyatakan bahwa konten pembelajaran yang disajikan melalui SMS cukup membantu hingga sangat membantu dalam memahami materi yang disajikan di kelas. Data lain menunjukan 90.70% setuju dan sangat setuju bahwa konten yang disajikan melalui SMS dapat mengingatkan kembali materi pelajaran yang telah dipelajari di kelas.